Parâmetros seminais, ultraestruturais, criopreservação e androgênese de espécies do gênero Brycon ameaçadas de extinção - Faustino, Francine [UNESP] (2014)
The doctoral thesis consisted of three main chapters besides the “General Introduction”, which includes a bibliographic review of the species studied and the topics discussed, and the “Final Remarks”. Scientific research articles will be published from the data of the three chapters in the scientific journals listed in the index. The first scientific article (Chapter I) describes the seminal parameters and the spermatozoa structure of Brycon vermelha, “vermelha” (Characiformes, Characidae). The semen of the Brycon vermelha is viscous and contains, in average, 4.34 ± 0.75x1010 spermatozoa.mL-1. Spermatozoa motility was of short duration when activated with distilled water, 46.48 ± 0.07 seconds until 100% of spermatozoa lost their motility. Scanning transmission electron microscopy (STEM) of spermatozoa revealed three distinctive parts: head, middle piece and tail (flagellum). Each part was analysed in detail by transmission electron microscopy (TEM). The characteristics observed suggest that the spermatozoa of B. vermelha posses ancestral characteristics of fish that reproduce by external fertilization, and can thus be classified as “uniflagellate anacrosomal aquasperms”, or aquasperms Type I. These are the first reports on B. vermelha semen and spermatozoa and, therefore, could be used as a reference and benchmark for research studies using biotechniques such as cryopreservation and androgenesis. The second scientific article (Chapter II) describes the ultrastructural alterations of Brycon orbignyanus, “piracanjuba” (Characiformes, Characidae) spermatozoa after cryopreservation. Spermatozoa were cryopreserved for 1 day, 1 month or 1 year in solutions containing DMSO, methyl glycol and methanol. The ultrastructural analysis of the frozen-thawed spermatozoa revealed alterations varying from small damages to the different parts of the cell to total destruction of spermatozoa ...